(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The Sihwa Lake Tidal Power Plant, located on the west coast of South Korea, stands as a prominent example of integrating renewable energy production with environmental restoration. Initially conceptualized to address severe water quality degradation in Sihwa Lake during the 1990s, the plant was completed in 2011, enabling the exchange of seawater to improve the lake’s ecological conditions. Over the past decade, the plant has not only operated as a major source of clean energy but also provided insights into the interplay between tidal power generation and coastal environmental dynamics. Since the inception of its commercial operations, K-water has conducted extensive studies to monitor and assess changes in the aquatic environment of Sihwa Lake and its adjacent coastal areas. These efforts have included precise bathymetric surveys and detailed physical oceanographic investigations over several years. This comprehensive approach has aimed to understand both the immediate and long-term impacts of tidal power operations on the surrounding marine ecosystem. Additionally, a state-of-the-art real-time ocean environmental monitoring system has been established. This system integrates a range of advanced observation technologies, including microwave tide gauges, ocean-meteorological buoys, water quality monitoring buoys, HF-radar systems, and wave and wave direction sensors. The continuous data collection facilitated by these instruments has significantly contributed to a robust database, enabling detailed analyses of hydrodynamic patterns, water quality trends, and other key environmental parameters. This presentation at EWTEC aims to provide an overview of the findings accumulated over more than a decade of research. Key highlights will include the observed transformations in the water environment of Sihwa Lake, changes in the coastal marine ecosystem in the vicinity of the tidal power plant, and the operational implications for the integration of tidal energy generation with marine environmental management. By sharing these insights, we hope to contribute to the growing body of knowledge supporting sustainable tidal energy development and its potential to enhance coastal ecological resilience globally. This study underscores the importance of combining renewable energy projects with long-term environmental monitoring and adaptive management to maximize ecological and socio-economic benefits. The lessons learned from Sihwa Lake can serve as a valuable reference for future tidal energy initiatives worldwide.